Risk Mitigation of Academic Information System in XYZ University - Muhammad Haris Fadhillah (Faculty of Economics dan Business, Atma Jaya Makassar University, 2024)
Academic information system (AIS) is an asset that universities must have to facilitate the work of operators and services to students. Nowadays, there are several threats faced by AIS managers related to data and information storaged security, thus requiring good risk management to mitigate risks that arise in the future. This research uses the fault tree analysis (FTA) and failure mode effect analysis (FMEA) methods to mitigate risks that may occur in AIS. The results show that there are 9 potential risks with 18 risk impacts, of which 1 risk impact is categorized as high, 4 risks are categorized as medium, and 13 risks are categorized as low. Five risk impacts that are categorized as high and medium need to be further evaluated, there are computer failure (R1), computer viruses (R2), external parties breaking into AIS (R7), capacity being full (R9), and server failure (R11).